Preparation of Sheepskin Unhairing Extracts from Locally Available Plants: Cleaner Leather Processing - Zerihun Teshome; Fitsum Etefa Ahmed; Tamrat Tesfaye; Lioul Getachew; Awoke Fenta Wodag; Misganaw Bitew (Journal of Engineering)
Leather is made from animal hides and skins that have passed through several stages of processing, from soaking to finishing. Unhairing is a crucial processing stage in which hair is removed from the animal hide or skin through open up the hair and it facilitates subsequent operations. The conventional sodium sulfide-based unhairing process generates a high volume of effluent, which accounts for 50 to 70% of the total biochemical oxygen demand (BOD) and chemical oxygen demand (COD) load in the tanneries’ effluent. This study aimed to investigate the potential of unhairing agents prepared from locally available plants. The research employed qualitative methods. Plant materials are collected, dried, and ground. In different proportions, unhairing extracts were obtained from Phytolacca dodecandra leaves, Cucurbita foetidissima fruits, and Solanum incanum fruits. In the conventional soaking process, plant extracts were applied in various concentrations to sheepskin. The physical parameters of conventionally processed (control) and experimentally treated leather were examined using FTIR, SEM, tear strength, percentage of elongation, and organoleptic tests. The unhairing solution was prepared from a mixture of 0.5% S. incanum extract, 0.5% P. dodecandra extract, 0.6% C. foetidissima extract, and 260 g/L lime powder lime, and this solution effectively removed the hair from the sheepskin in both hairs saving and hair burning unhairing process. The study revealed that the sheepskin treated with the plant extracts based on an unhairing agent and the conventional unhairing agent showed a comparable tensile strength (42.3 kg/cm and 45.2 kg/cm), tear strength (140.1 kg/cm2 and 143.5 kg/cm2), and percent elongation at break (40.2 and 42.3), respectively, which were above the permissible limit for leather production making. According to the study findings, the plant extracts have a good potential for removing hair from sheepskin, and they are eco-friendly and cost-effective compared to unhairing chemicals such as sodium sulfide.